DAMPAK PERUBAHAN IKLIM TERHADAP HASIL TANAMAN PADI DI KAWASAN DANAU SINGKARAK - Yummama Karmaita (Faculty of Agriculture, Universitas Malikussaleh, 2018)
This study aims to: (a) see the results of several genotypes of rice crops grown on paddy fields with drought stress, (b) to obtain the type of paddy rice genotype in drought-affected paddy fields. This research was conducted in Simusan rice field, Rambatan sub-district, Tanah Datar district and Laboratory of Agriculture Faculty, Andalas University, West Sumatra. This research used Randomized Block Design (RBD) method using 7 rice genotypes, 6 rice field genotypes and 1 genotype of upland rice as a comparison. If F value is greater than F table 5% it needs to be continued using Tukey test at 5%. The results revealed that in general, all the rice genotypes tested in showed good results on paddy fields that suffered drought stress, where all these genotypes showed a significantly different effect on the number of productive tillers, panicle length, number of grains per panicle, the percentage of unpaid grain per panicle.